Corrected Trapezoidal Rule For The Riemann-Stieltjes Integral - Rike Marjulisa; M Imran; Ayunda Putri (Diponegoro University, 2025)
This study investigates the derivation of a corrected trapezoidal rule for approximating the Riemann-Stieltjes integral. The corrected trapezoidal rule is derived by approximating certain monomial functions to obtain optimal method coefficients. The proposed method has an accuracy of order three. Furthermore, an error analysis is conducted to assess the accuracy of the obtained approximation. In the final section, numerical computations are presented to compare the performance of the proposed method with existing methods. The results demonstrate that the proposed method produces smaller errors compared to previously developed approaches.